Impact of coronary stent pricing regulation in a private sector health care system in India: a retrospective cohort analysis - Nadar, Shijin N.; Anney, Nirav; Khan, Irfan H. (International Journal Of Community Medicine And Public Health, 2020)
Background: National pharmaceutical pricing authority of India slashed prices of coronary stents by up to 80% (February 2017) to increase affordability of percutaneous coronary interventions (PCI). This study aimed to assess its impact. Methods: A retrospective cohort study in a private sector tertiary care hospital in Mumbai, India evaluating data of patients admitted for PCI from 13 February 2015 to 12 January 2019. Cost of undergoing PCI before and after price capping of coronary stents was analysed and studied under different subgroups along with other associated parameters. Results: Of 1015 patients included, 514 of them underwent PCI before and 497 after the price capping. 967 stents at an average 1.88 stents/case and 1011 stents at average 2.03 stents/case were implanted before and after the price capping respectively. Cost of PCI decreased by 11.64% and 28.14% in non GIPSA (private insurance providers and self-paying) and GIPSA (public sector insurance providers) category respectively under single room class and by 2.79% and 19.87% in non GIPSA and GIPSA category respectively under twin sharing room class. In multi sharing room class cost of PCI increased by 3.99% in non GIPSA category and decreased by 26.87% in GIPSA category. Usage of adjunct devices and number of complex PCIs increased significantly. Conclusions: Cost of undergoing PCI has dropped significantly after price regulation of coronary stents in most subgroups despite increased usage of adjunct devices like IVUS, FFR/iFR for better patient outcomes. There was no effect on number of PCIs performed.